Acute posterior multifocal placoid pigment epitheliopathy (APMPPE) – a report of three cases - Wilkos-Kuc, Agnieszka; Biziorek, Barbara; Żarnowski, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: The aim of this study is to present and discuss three cases of acute posterior multifocal placoid pigment epitheliopathy (APMPPE). Material and methods: Three young patients (one woman and two men), developed rapid loss of vision in one or both eyes. Basic ophthalmic examination and additional diagnostic methods including: fluorescein angiography (FA), indocyanine green angiography (ICG), optical coherence tomography (OCT) and human leucocyte antigen (HLA) class I test were performed. Results: Based on the results of performed investigations the diagnosis of acute posterior multifocal placoid pigment epitheliopathy (APMPPE) was established. Fundus examination revealed characteristic multifocal, placoid, creamy or grey/white subretinal lesions. Fluorescein angiography in acute stage of the disease demonstrated early hypofluorescence followed by later hyperfluorescence of the lesions. Indocyanine green angiography demonstrated hypofluorescence in all stages of the angiogram. In one case, class I HLA-B7 antigen was found. In all presented cases visual acuity markedly improved with general glicocorticosteroids. Conclusions: Acute posterior multifocal placoid pigment epitheliopathy (APMPPE) is characterized by rapid, but transient loss of visual acuity. Diagnosis is established in fluorescein angiography and prognosis for recovery is good, however in cases with poor visual acuity glicocorticosteroids might be beneficial.